1970
DOI: 10.3329/bmrcb.v37i2.8437
|View full text |Cite
|
Sign up to set email alerts
|

Eclampsia-scenario in a hospital- a ten years study

Abstract: This cross sectional record based institutional study was conducted in the Department of Obstetrics & Gynaecology, Burdwan Medical College, Burdwan over ten years (1999-2008) aiming analysis of eclamptic mothers for evaluation of maternal and perinatal outcome with different anticonvulsant medications. Total 5991 pregnant mothers with eclampsia admitted in the inpatient department of the tertiary care teaching hospital were recruited for the study, irrespective of their previous antenatal check up history.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
20
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 3 publications
6
20
5
Order By: Relevance
“…Unbooked pregnancy is a high risk factor for eclampsia as proved in various studies. Vijayasree et al (2015), Pal A et a (2011) and Tan K H et al (2006) had 64.3%, 77.5% and 64.3% unbooked cases respectively which was comparable with the present study [20] .…”
Section: Socio-demographic Characteristicssupporting
confidence: 90%
“…Unbooked pregnancy is a high risk factor for eclampsia as proved in various studies. Vijayasree et al (2015), Pal A et a (2011) and Tan K H et al (2006) had 64.3%, 77.5% and 64.3% unbooked cases respectively which was comparable with the present study [20] .…”
Section: Socio-demographic Characteristicssupporting
confidence: 90%
“…Finally, 59 articles (20 from high‐income, 30 from middle‐income and nine from low‐income countries) were eligible for this review (Fig. ) …”
Section: Resultsmentioning
confidence: 99%
“…Figure shows the summary of all the studies that reported type of eclampsia at three levels (antepartum, intrapartum and post‐partum) . Out of 18 488 eclampsia cases, the proportion of antepartum, intrapartum and post‐partum eclampsia was 59%, 20% and 21%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…If we see the time trend of eclampsia patients came in 2015, it can be concluded that in the month of January, October, November, December there were more number of eclampsia patients than the rest of the months ( Figure 1). 4,7,[13][14][15][16][17] Present study revealed that almost 40.7% were un-booked cases suggesting irregular antenatal care, but the study conducted by Pal et al found much lesser proportion whereas Pradeep et al (88%) and Sunita et al (95%), Das (90.09%), Singh et al (90.5%) found much higher proportions. 6,4,13,9,17 Eclampsia was common in young pregnant woman who were less than 25 years (80.9%) in the present study, which was comparable to findings of 4,14,9,7,17,15 Eclampsia was more in Primi-gravida women (68%).…”
Section: Resultsmentioning
confidence: 86%